ANALISIS RASIO LIKUIDITAS, PROFITABILITAS DAN SOLVABILITAS TERHADAP KINERJA KEUANGAN PT. SUMBER ALFARIA TRIJAYA TBK. PERIODE 2020-2024 - Fitriani, Nurhalisa; Aisyah, Siti; Septiani Amin, Ameli Rezki (LPPM - STIE SAKTI ALAM KERINCI, 2026)
This study aims to determine the impact of liquidity, profitability, and solvency ratios on the financial performance of PT. Sumber Alfaria Trijaya Tbk. for the 2022-2024 Period. The research method used is quantitative. The population in this study is the financial statements published by PT. Sumber Alfaria Trijaya Tbk. The samples taken in this study are the balance sheet, income statement, and notes to the financial statements of PT. Sumber Alfaria Trijaya Tbk. Data analysis uses quantitative descriptive techniques utilizing financial ratio analysis methods. The results of the analysis and assessment indicate that the financial performance of PT. Sumber Alfaria Trijaya Tbk. The 2022-2024 period, based on liquidity, profitability, and solvency ratios, can be considered quite healthy. However, improvements are still needed, particularly in asset management, operational efficiency, and debt control, to ensure optimal financial performance in the future. Keywords : Liquidity Ratio, Profitability Ratio, Solvency Ratio, Financial Performance